Effect of 150 kHz electromagnetic radiation on the development of polycystic ovaries induced by estradiol Valerate in Sprague Dawley rats - Stephanie Mohammed; Venkatesan Sundaram; Nikolay Zyuzikov (BMC, 2021)
Abstract Background Polycystic ovary syndrome (PCOS) is the most common complex endocrine disorder affecting approximately 2-20% of reproductive aged females. Tumour Treating Fields (100-300 kHz) is a recent innovative, non-invasive therapeutic approach to cancer therapy. This frequency as an alternative therapy for the management of polycystic ovaries has not yet been explored. Objectives To explore the effect of full-body exposure of 150 kHz Electromagnetic Radiation (EMR), on the development of polycystic ovaries in an estradiol valerate-induced PCO rat model. Method Twenty-one female adult rats were divided into three groups (n = 7 each): control, Estradiol Valerate (EV) and EV + EMR groups. The EV + EMR group was subjected to full body exposure at 150 kHz EMR continuously for eight consecutive weeks. Estradiol valerate was administered orally to induce polycystic ovaries in EV and EV + EMR groups. Body and ovarian weights were recorded and analysed. The regularity of the estrous cycle was assessed in all three groups. The histological study of ovarian tissue was carried out by haematoxylin and eosin staining. The serum concentration levels of Luteinizing Hormone (LH), Follicle-Stimulating Hormone (FSH) and testosterone were measured using the ELISA method. Results The body and ovary weights did not differ significantly between the EV and EV + EMR groups. The estrous cycle was found to be irregular in both the EV and EV + EMR groups. Ovarian histology revealed near normal morphology with little or no degenerative and morphological changes in developing follicles in the exposed group. Histometrical analysis showed an increased number of developing follicles and a significant reduction in the number and size of follicular cysts (p < 0.05) in the EV + EMR group. Hormonal analysis revealed no significant difference in the testosterone and FSH levels between the EV + EMR and EV groups. However, the LH, LH/FSH ratio decreased significantly in the EV + EMR group compares to the EV group. Conclusion The 150 kHz EMR appear to have little or no degenerative and morphological changes in the developing follicles, an increased number of typical developing follicles and a significant reduction in the number and size of the follicular cysts (p < 0.05).